Exposure of Infants to Isoniazid via Breast Milk After Maternal Drug Intake of Recommended Doses Is Clinically Insignificant Irrespective of Metaboliser Status. A Physiologically-Based Pharmacokinetic (PBPK) Modelling Approach to Estimate Drug Exposure of Infants via Breast-Feeding - Garessus, Estella Dora Germaine; Mielke, Hans; Gundert-Remy, Ursula (Frontiers in Pharmacology, 2019)
Isoniazid is a first-line anti-tuberculosis drug recommended for treatment of drug-susceptible M. tuberculosis infections. Breast-feeding is not contra-indicated while undergoing isoniazid therapy, even though isoniazid was found to migrate into breast milk, leading to infant drug exposure. Exposure assessment of isoniazid in infants exposed to the drug via breast milk has so far not accounted for the polymorphic expression of the isoniazid metabolizing enzyme N-acetyltransferase 2. The aim of this study was to re-visit the safety assessment of maternal isoniazid therapy for infants exposed to the drug via breast milk, while accounting for fast and slow metabolizers in the adult and infant population, as well as for slower metabolism in small infants than in adults. We applied a physiologically-based pharmacokinetic (PBPK) modelling approach to estimate mother and infant external and internal drug exposure non-invasively. Validity of our PBPK models was confirmed through comparison of simulated results with experimental data. Highest recommended oral doses for mothers are daily 300 mg or 900 mg every three days. Simulation of maternal intake of 300 mg resulted in oral exposures of 0.58 (95%CI: 0.42-0.69) mg/day and 1.49 (1.22-1.50) mg/day for infants of fast and slow metabolizing mothers, respectively. Oral exposures of infants within the first 24 h after maternal intake of 900 mg were 1.75 (1.25-2.06) mg/day and 4.46 (4.00-4.50) mg/day. Maximal drug concentrations in infant plasma ranged between 0.04 mg/L and 0.78 mg/L for the two dosing regimens. We therefore conclude that infant exposure to isoniazid via breast milk after maternal drug intake of highest recommended doses is very low. We expect that such low exposure levels most likely do not cause any clinically significant adverse effects in nursed infants.